Effects of artificial illumination on drinking bats: a field test in forest and desert habitats. (27th August 2018) - Russo, D.; Ancillotto, L.; Cistrone, L.; Libralato, N.; Domer, A.; Cohen, S.; Korine, C.
Abstract: Bats show pronounced and often‐adverse reactions to artificial illumination at night (ALAN) when commuting, roosting or foraging. ALAN also affects bat drinking activity, at least when lighting occurs over short intervals. We tested whether continuous illumination of drinking sites over 4‐h periods would lead bats to tolerate ALAN and resume drinking in the course of the night. We conducted our experiments in forest (Italy) and desert (Israel) sites to test whether in the latter habitat, where water is scarce, a greater motivation to drink might lead to less adverse bat reactions. We recorded 6853 drinking buzzes and 1647 feeding buzzes from 17 species and one species group. In the forest sites, species that hunt in open spaces or along forest edges showed little ( P. pipistrellus and H. savii ) or no ( P. kuhlii and N. leisleri ) drinking activity decrease, while those associated with forest interiors ( Barbastella barbastellus, Plecotus auritus and bats in the genus Myotis ) exhibited a strong negative response. In the desert sites, all studied species reduced drinking activity, yet in the desert populations of P. kuhlii we recorded stronger adverse reactions only far from human settlements. The harsh reactions that the desert bat species showed towards ALAN rule out any effect of a greater motivation to drink. Illumination had no effect on foraging by most species, except in the forest sites, where Pipistrellus kuhlii and Nyctalus leisleri increased foraging when the light was on, and in the desert sites, where Hypsugo bodenheimeri decreased foraging in such situations. The progressive human encroachment that is taking place in many world regions on both forests and especially deserts, where few sites for drinking are available, may jeopardize bat populations also through increased exposure to ALAN. Abstract : We tested reactions of drinking bats to continuous illumination of drinking sites over 4‐h periods in forest (Italy) and desert (Israel) sites and hypothesized that in the latter habitat, where water is scarce, a greater motivation to drink might lead to less adverse responses. We found that artificial illumination seriously affected bat drinking behaviour, especially that of forest specialists and desert species. The increasing human encroachment that is taking place in many world regions on both forests and especially deserts, where few drinking sites are available, may jeopardize bat populations also through increased exposure to artificial lighting.